Data from: Cold winters drive consistent and spatially synchronous 8-year population cycles of cabbage stem flea beetle - Emery, Sara; Lundin, Ola (Swedish University of Agricultural Sciences, 2022)
The data contain information on the number of cabbage stem flea beetle (Psylliodes chrysocephala) larva in winter oilseed rape plants in southern Sweden 1968-2018. A monitoring program for cabbage stem flea beetles in southern Sweden winter oilseed rape fields started in 1969. These data were collected over a 50-year period from commercial winter oilseed rape fields across Scania, the southernmost county in Sweden, by the Swedish University of Agricultural Sciences and its predecessors as well as the Swedish Board of Agriculture. The sampling region of Scania, Sweden was divided into five subregions: (1) southeast, (2) southwest, (3) west, (4) northeast, and (5) northwest. For each subregion we also include data on daily maximum and minimum temperature data in Celsius from 1968-2018. The total area planted to winter oilseed rape in Scania, the mean regional number of cold days and the North Atlantic Oscillation index are reported. Lastly, P. chrysocephala density in winter oilseed rape across five subregions in the UK from 2001-2020 are extracted from a plot in a public report and reported.

The data in the CSFB_Scania_NAs2010-11.csv file have information on crop planting date, the total number of P. chrysocephala larvae detected, number of plants sampled, the density of larva (total larvae/plants examined), sampling date, year, subregion, whether a seed coating or spray pesticide was used in the field and whether the sample was from a commercial field or from an experiment. 3118 rows.

Five files have daily maximum and minimum temperatures for each subregion 1968-2018 (NorthwestInsectYear.csv, NortheastInsectYear.csv, SoutheastInsectYear.csv, SouthwestInsectYear.csv, WestInsectYear.csv). All weather data comes from Swedish weather data website https://www.smhi.se/data. 18,566 rows in the NorthwestInsectYear.csv, 18,606 rows in the NortheastInsectYear.csv, 18,574 rows in the SoutheastInsectYear.csv, 18,574 rows in the SouthwestInsectYear.csv, 18,574 rows in the WestInsectYear.csv.

The file WOSRareaSkane1968-present.csv pulls data from the Swedish Board of Agriculture on the number of hectares planted to winter oilseed rape, turnip rape and the combined total in the Scania region in Sweden from 1968 (matching with harvest year 1969) to 2019. 53 rows.

The file NAO_coldDays.csv gives the annual Hurrell PC-Based North Atlantic Oscillation Index value from https://climatedataguide.ucar.edu/climate-data/hurrell-north-atlantic-oscillation-nao-index-pc-based as well as the raw and log-transformed regional mean number of cold days (below -10C) per year for Scania. 51 rows.

Finally, the data in the CSFBinUK2001-2020.csv is the data extracted from “historical comparisons” figure from the Crop Monitor report last accessed 7 November, 2022 at https://www.cropmonitor.co.uk/wosr/surveys/wosrPestAssLab.cfm?year=2006/2007&season=Autumn. These data include the regions in the UK that data was collected from, the harvest year and the mean number of cabbage stem flea beetle larvae counted per plant in each region and year. 101 rows.

Data innehåller information om antalet rapsjordloppor i höstoljeväxter i Skåne 1969-2018 tillsammans med information om fältens skötsel, provtagningsförhållanden, väder, oljeväxtarealer mm. En mer utförlig beskrivning ges på engelska.

Datasetet består huvudsakligen av information om förekomsten av larver av rapsjordloppa i höstrapsfält i Skåne som samlats in under 50 år. En beskrivning av varje fil och hur filerna förhåller sig till varandra ges på engelska. En mer detaljerad beskrivning av varje variabel ges också i dokumentationsfilen readme.txt.
Data från: Kalla vintrar driver konsekventa och rumsligt synkrona 8-åriga populationscykler hos rapsjordloppa
Keywords: crop protection; växtskydd; rape (plant); raps; weather; väder; pest; skadegörare; population cycle; populationscykel; cabbage stem flea beetle; rapsjordloppa; Psylliodes chrysocephala; Ecology; Ekologi; Agricultural Science; Jordbruksvetenskap; Farming; Areella näringar; Biota; Biologi och ekologi